Cannabidiol Vaping–Associated Multifocal NSCLC in a 24-Year-Old Female: A Case Report - Mansi Barthwal, MD; Nataliya Moldovan, MD; Shantanu Banerji, MD; Julian O. Kim, MD (JTO Clinical and Research Reports)
Vaping use among Canadian youth is rising but the long-term sequelae of cannabidiol (CBD) vaping are not yet elucidated. Vaping aerosols contain carcinogens; however, owing to the latency period between carcinogen exposure and clinical presentation of malignancies, at present, there is a paucity of reported CBD vaping–associated lung cancers. We present the case of a 24-year-old female with nonspecific respiratory symptoms who developed multifocal NSCLC attributable to extensive CBD vaping.